2013
DOI: 10.1111/jnc.12135
|View full text |Cite
|
Sign up to set email alerts
|

Ly6C+Ly6G Myeloid‐derived suppressor cells play a critical role in the resolution of acute inflammation and the subsequent tissue repair process after spinal cord injury

Abstract: Acute inflammation is a prominent feature of central nervous system (CNS) insult and is detrimental to the CNS tissue. Although this reaction spontaneously diminishes within a short period of time, the mechanism underlying this inflammatory resolution remains largely unknown. In this study, we demonstrated that an initial infiltration of Ly6C + Ly6G À immature monocyte fraction exhibited the same characteristics as myeloid-derived suppressor cells (MDSCs), and played a critical role in the resolution of acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 48 publications
(52 reference statements)
3
72
0
Order By: Relevance
“…Our findings are in agreement with other studies reporting that Arg-1 could attenuate the function of iNOS, inhibit NF-κB activation and inflammatory cytokines in vitro , and decrease macrophage infiltration and inflammation in vivo in a rabbit model of atherosclerosis (22). MDSCs played a critical role in the resolution of acute inflammation and tissue repair caused by spinal cord injury (30) and were found to modulate macrophage activation toward an immunosuppressive phenotype through Arg-1 (31). Whether early protection of Arg-1 + MDSC by soy isoflavones plays a role in altering molecular pathways involved in radiation-induced inflammation such as NF-κB activation and pro-inflammatory cytokine production remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in agreement with other studies reporting that Arg-1 could attenuate the function of iNOS, inhibit NF-κB activation and inflammatory cytokines in vitro , and decrease macrophage infiltration and inflammation in vivo in a rabbit model of atherosclerosis (22). MDSCs played a critical role in the resolution of acute inflammation and tissue repair caused by spinal cord injury (30) and were found to modulate macrophage activation toward an immunosuppressive phenotype through Arg-1 (31). Whether early protection of Arg-1 + MDSC by soy isoflavones plays a role in altering molecular pathways involved in radiation-induced inflammation such as NF-κB activation and pro-inflammatory cytokine production remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Studies have demonstrated a suppressive effect of MDSC on NK cells through cell contact-dependent mechanisms [2][3][4][5] ; moreover, MDSC might play an immunosuppressive role in NK cell activation, exacerbating macrophage polarization toward an M2 phenotype. 6 To generate a more permissive microenvironment for NK cell activation by aerosolized TLR agonists, we tested the possibility that delivery of nebulized RB6-8C5 antibody, reported to reduce both monocytic and granulocytic subsets from circulating blood, 14 locally depletes MDSC. Indeed, flow cytometry analysis of enzymatically digested lungs of C57BL/6 mice injected i.v.…”
Section: Resultsmentioning
confidence: 99%
“…14 Airway-delivered RB6-8C5 antibody, directed to both Ly6G and Ly6C, at 72-96 h interval effectively depleted MDSC recruited in the lung tumor microenvironment at a dose 4-to 8-fold lower than that used in systemic administration, 14,19 improving antitumor effects of aerosolized TLR agonists. Although RB6-8C5 antibody is not only MSDCs specific, but can also target other Ly6G-or Ly6C-expressing cells, at a late time point of the experiment no differences in the percentage of macrophages, DCs , monocytes and CD8 C T cells were observed in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…injected to mice three times at days 21 (24 h prior to immunization), 0 (the day of immunization), and 1 (the day after immunization) (26)(27)(28)(29)(30).…”
Section: In Vivo Depletion Of Mdscsmentioning
confidence: 99%